Timing Pulsars with CHIME and the NANOGrav 15yr Dataset - Agazie, Gabriella Yehenew (Proceedings of the Wisconsin Space Conference, 2023)
The North American Nanohertz Observatory for Gravitational Waves (NANOGrav) conducts long-term timing campaigns on large numbers of millisecond pulsars (MSPs). Wideband (WB) timing of the NANOGrav datasets was first done in the 12.5yr dataset, and proved to be extremely helpful for measuring the time-varying dispersion measure, which can significantly limit timing precision. However, we are limited by the fact that NANOGrav only observes most pulsars once per month. In contrast, the Canadian Hydrogen Intensity Mapping Experiment (CHIME) Telescope currently observes most NANOGrav MSPs at nearly daily cadence at 600 MHz with a 400 MHz bandwidth. Using WB timing techniques, we combined one year of data taken at CHIME with data over the same time period from the NANOGrav 15yr Dataset for three MSPs.